2001
DOI: 10.1155/2001/401309
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Impact of Irritable Bowel Syndrome in Canada

Abstract: Irritable bowel syndrome (IBS) is the most common functional gastroenterological disorder reported to physicians. In Canada, its prevalence is about 6%. In the United States and the United Kingdom, the prevalence is estimated to be closer to 15%. Patients with IBS tend to make extensive use of health care services, even though a high percentage of them do not seek medical advice. The costs of IBS are a large expenditure of scarce resources. These costs can be divided into several categories: direct, indirect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Other GI symptoms, such as bloating and distension, are also considered to be consistent with a diagnosis of FBDs such as IBS. With a prevalence of about 10% , IBS is one of the more common GI disorders in our society, imposing a very high economic burden in North America (8). …”
Section: Definitions Of Celiac Disease and Irritable Bowel Syndromementioning
confidence: 99%
“…Other GI symptoms, such as bloating and distension, are also considered to be consistent with a diagnosis of FBDs such as IBS. With a prevalence of about 10% , IBS is one of the more common GI disorders in our society, imposing a very high economic burden in North America (8). …”
Section: Definitions Of Celiac Disease and Irritable Bowel Syndromementioning
confidence: 99%
“…Despite the lack of structural anomalies, patients with FD may display upper abdominal pain, bloating, fullness, and tenderness on palpation (Talley et al, 2005;Saad and Chey, 2006;Tack et al, 2006), and patients with IBS may display lower abdominal pain, diarrhea, constipation, and bloating (Longstreth et al, 2006;Mayer, 2008). Functional dyspepsia and IBS are estimated to occur in about 15% (Saad and Chey, 2006) and 10 to 15% (Boivin, 2001;Quigley et al, 2006), respectively, of the general population in Western countries, and the underlying mechanisms remain to be fully clarified. Some associations between FD and Helicobacter pylori infection have been considered in the elderly in Western countries (Talley et al, 2005;Saad and Chey, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates for IBS vary widely among different geographic regions [2]. Epidemiological studies have revealed that the estimated lifetime prevalence rate for the IBS ranges from 6% to 46% worldwide [3][4][5]. In Taiwan, the prevalence rate is between 17.5% and 22.1%, and nearly 50% of the patients with IBS symptoms consult physicians [6].…”
Section: Introductionmentioning
confidence: 99%